An Experimental Study of Influences of Performance-Related Payments on Timing of Delegated Stock Purchases. Issue 1 (2nd January 2017) - Gärling, Tommy; Andersson, Maria; Hedesström, Martin; Biel, Anders
ABSTRACT: Performance-related bonuses are important tools for investment organizations to incentivize stock traders. Yet, two experiments indicate that bonuses rewarding short-term performance may lead to worse timing of purchases. The authors propose that hyperbolic time discounting makes participants set lower aspired purchase prices for short-term (decreasing percentage) bonuses than for long-term (increasing percentage) bonuses. For this reason purchases are made earlier for decreasing than increasing percentage bonuses, earlier for decreasing than random prices, and earlier for high price volatility than for low price volatility. Neither purchases at the lowest price or highest bonus are attained. Hyperbolic time discounting may account for bubbles observed in experimental double-auction markets.